The Great Depression of Debt: Survival Techniques for Every Investor - Brussee Warren (John Wiley, 2008)
In 2004, Warren Brussee wrote, "Come 2008, the number of people giving up on making house payments will skyrocket . . . banks will be forced to foreclose on homes and sell them, causing a glut of homes on the market and a deflation of home values. . . . You will be able to get a great deal on a used SUV, especially a Hummer!"